Muscle building supplement use in Australian adolescent boys: relationships with body image, weight lifting, and sports engagement - Zali Yager; Siân McLean (BMC, 2020)
Abstract Background The extent and implications of muscle building protein supplement use among adolescents is relatively unknown. This study aimed to describe the prevalence of protein powder, creatine, and anabolic steroid use in a sample of 14-16 year-old boys in Australia, and the predictors of actual use, and intentions to use protein powder. Methods Data were obtained from questionnaires with Australian adolescent boys aged 14-16 years from one independent boy's school in Melbourne (N = 237). Hierarchical linear and logistic regressions were used to determine the predictors of intentions, and actual use of protein powder. Results 49.8% of boys reported current use of, and 62% intended to use protein powder; 8.4% used creatine, and 4.2% used anabolic steroids. Higher levels of drive for muscularity, participation in weight training, and playing a greater number of sports were significant predictors of higher current use and intentions to use protein powder, but age, BMI, body esteem, and ethnicity were not. Conclusions Prevalence of muscle building supplement use was relatively high among this adolescent population. This research has implications for intervention and prevention programs to educate young boys about muscle building supplements to reduce negative physical and psychological health effects of their use.